Membentuk Citra Diri Mahasiswa Universitas Amikom Yogyakarta Melalui Media Sosial Instagram - Ari, Muhammad; Sekarningrum, Anggun Anindya (Unitri Press, 2025)
The development of digital technology has changed interaction patterns, making Instagram the dominant platform for identity construction of the younger generation. For AMIKOM University Yogyakarta students who are active in digital media and in the stage of self-discovery, Instagram has become a space for self-expression and imaging. This study analyzes the process of forming these students' self-image on Instagram and identifies key influencing factors. Using a phenomenological approach, this qualitative study involved in-depth interviews, observation of account activities, and documentation on three informants selected through purposive sampling based on the intensity of Instagram usage and campus involvement. Data analysis was conducted through thematic coding techniques to formulate each informant's digital narrative. The findings reveal three orientations of self-image formation: (1) professional-academic-educative content and achievements (Putri, 9,744 followers); (2) authentic-personal-honest self-expression (Olivia, 5,140 followers); and (3) creative-artistic-innovative uploads (Candra, 2,354 followers). The three main driving factors include: the cognitive need to share academic knowledge; self-actualization through creative expression that combines technical expertise with artistic vision; and the need for social existence for digital validation through community interaction and engagement metrics. The findings confirm the relevance of Self-Image Theory (Baumeister, 1999) and Social Identity Theory (Tajfel & Turner, 1979) in the context of modern social media. The research results are expected to help the development of digital literacy and personal branding strategies in the campus environment. Abstrak Perkembangan teknologi digital telah mengubah pola interaksi, menjadikan Instagram platform dominan konstruksi identitas generasi muda. Bagi mahasiswa Universitas AMIKOM Yogyakarta yang aktif di media digital dan dalam tahap pencarian jati diri, Instagram menjadi ruang ekspresi diri dan pencitraan. Penelitian ini menganalisis proses pembentukan citra diri mahasiswa tersebut di Instagram dan mengidentifikasi faktor kunci yang mempengaruhi. Dengan pendekatan fenomenologi, studi kualitatif ini melibatkan wawancara mendalam, observasi aktivitas akun, dan dokumentasi pada tiga informan terpilih melalui purposive sampling berdasarkan intensitas penggunaan Instagram dan keterlibatan kampus. Analisis data dilakukan melalui teknik coding tematik untuk merumuskan narasi digital setiap informan. Hasil temuan mengungkap tiga orientasi pembentukan citra diri: (1) profesional-akademik—konten edukatif dan prestasi (Putri, 9.744 pengikut); (2) autentik-pribadi—ekspresi diri jujur (Olivia, 5.140 pengikut); dan (3) kreatif-artistik—unggahan inovatif (Candra, 2.354 pengikut). Tiga faktor pendorong utama meliputi: kebutuhan kognitif berbagi pengetahuan akademik; aktualisasi diri melalui ekspresi kreatif yang memadukan keahlian teknis dengan visi artistik; serta kebutuhan eksistensi sosial untuk validasi digital lewat interaksi komunitas dan metrik engagement. Temuan ini menegaskan relevansi Teori Citra Diri (Baumeister, 1999) dan Teori Identitas Sosial (Tajfel & Turner, 1979) dalam konteks media sosial modern. Hasil penelitian diharapkan membantu pengembangan literasi digital dan strategi personal branding di lingkungan kampus.